Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.jvlc.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A pandemic influenza modeling and visualization tool

Abstract: a b s t r a c tThe National Strategy for Pandemic Influenza outlines a plan for community response to a potential pandemic. In this outline, state and local communities are charged with enhancing their preparedness. In order to help public health officials better understand these charges, we have developed a visual analytics toolkit (PanViz) for analyzing the effect of decision measures implemented during a simulated pandemic influenza scenario. Spread vectors based on the point of origin and distance traveled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 31 publications
1
52
0
Order By: Relevance
“…These models can be used to simulate the behavior of a system changing over time which is initially characterized by the original data and can be controlled by the user by means of parameter refinements. Examples of models in the domain of epidemic research include [11], [12] and [13]. In brief, models drive the transformation of the data to be used for visualizations and "provide a basis for decision makers to understand their world" [14].…”
Section: B Visual Analyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…These models can be used to simulate the behavior of a system changing over time which is initially characterized by the original data and can be controlled by the user by means of parameter refinements. Examples of models in the domain of epidemic research include [11], [12] and [13]. In brief, models drive the transformation of the data to be used for visualizations and "provide a basis for decision makers to understand their world" [14].…”
Section: B Visual Analyticsmentioning
confidence: 99%
“…Another popular visualization and modelling tool to support decision-making in the domain of public health is PanViz [13]. It is an influenza simulation tool that uses spatio-temporal views to help public health officials understand the impact of decisions over the disease spread.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, in the visual analytics research as a whole, it is usual to address one of the tasks, and only a few works address two of them [1] [46][55] [64]. Our work gives a first example of how all three tasks can be supported as a single workflow.…”
Section: How This Work Extends the State Of The Artmentioning
confidence: 99%
“…Regarding economic studies, for example, costeffectiveness analyses of influenza vaccination were first reported in the US in 1997 [27], and later in 2003 in the Netherlands, together with mathematical modelling [31]. Following the 2009 pandemic, the use of these studies, jointly risk and uncertainty assessments, were frequently reported in European countries, the US, and Canada [32][33][34]. Table 1 summarizes the information and factors by segment of the policy chain and gives examples of countries that emphasised them as having a strong impact in the decision-making process of influenza vaccination policy.…”
Section: Information Influencing Decisions and Other Factorsmentioning
confidence: 99%